Keanekaragaman Fitoplankton dan Kaitannya Dengan Kondisi Perairan di Senggarang Besar, Kota Tanjungpinang, Kepulauan Riau - Efrina Yanti; Tri Apriadi; Andi Zulfikar (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2024)
ABSTRACTThe existence of phytoplankton in water can provide information about the state of the waters. Changes in water quality can be seen from the abundance and composition of phytoplankton. The purpose of this study was to determine the diversity of phytoplankton, to determine the relationship between the abundance of phytoplankton and environmental conditions, to determine the quality of the waters based on the diversity of phytoplankton in Senggarang Besar. The research method used is a survey method. This study took 10 sampling points with the Systematic Random Sampling method. Data analysis used is an ecological index, multiple regression lines, correlation, and ANOVA. The diversity index value in the waters of Senggarang Besar Tanjungpinang City is in the low category, with the results of identifying phytoplankton from the whole weekly found 3 divisions with 21 genera, the three divisions include Bacillariophyta (18 genera), Dinophyta (2 genera), and Chlorophyta (1 genus). The parameter that has the highest correlation with the abundance of phytoplankton is the parameter of nitrate (NO3), while the comparison of the abundance of phytoplankton per week in Senggarang Besar waters shows that the combination between the first week and the second week is very significantly different, the combination of the first week with the third week is very significantly different and the combination is significantly different in the second and third week. Based on the saprobic index in Senggarang Besar waters, it is categorized into the class of oligosaprobic/very light organic matter pollution.Keywords: Diversity, Phytoplankton, Saprobic, Senggarang Besar Waters. ABSTRAKKeberadaan fitoplankton di suatu perairan dapat memberikan informasi mengenai keadaan perairan. Perubahan terhadap kualitas perairan dapat ditinjau dari kelimpahan dan komposisi fitoplankton. Penelitian ini dilakukan untuk mengetahui keanekaragaman fitoplankton, mengetahui kaitan antara kelimpahan fitoplankton dengan kondisi lingkungan dan kualitas perairan berdasarkan keanekaragaman fitoplankton di Senggarang Besar. Metode penelitian yang digunakan adalah metode survei. Penelitian ini mengambil 10 titik sampling dengan metode Sistematik Random Sampling. Analisis data yang digunakan yaitu indeks ekologi, regresi linier berganda, korelasi, dan ANOVA. Nilai indeks keanekaragaman di perairan Senggarang Besar Kota Tanjungpinang dalam kategori rendah, dengan hasil identifikasi fitoplankton dari keseluruhan perminggu ditemukan 3 divisi dengan 21 genera, ketiga divisi tersebut antara lain Bacillariophyta (18 genera), Dinophyta (2 genera), dan Chlorophyta (1 genus). Parameter yang berkorelasi paling tinggi terhadap kelimpahan fitoplankton adalah parameter nitrat (NO3). Perbandingan kelimpahan fitoplankton perminggu di Perairan Senggarang Besar menunjukkan bahwa kombinasi antara minggu pertama dan minggu kedua berbeda sangat nyata, kombinasi minggu pertama dengan minggu ketiga berbeda sangat nyata dan kombinasi pada minggu kedua dan minggu ketiga berbeda nyata. Berdasarkan indeks saprobik di perairan Senggarang Besar terkategori ke dalam golongan pencemaran bahan organik Oligosaprobik/sangat ringan.Kata kunci: Fitoplankton, Keanekaragaman, Perairan Senggarang Besar, Saprobik